The Impact of Strategic Planning on Crisis Management in a Public Organization in Qatar - Maharmeh, Thamer Mohammed (Journal of Risk and Crisis Management, 2021)
This research aimed at investigate the degree of effects of strategic planning and its dimensions (environmental analysis, vision and mission, strategic objectives and values, and projects and operational plans) on crisis management. Data was collected by using closed-ended survey from simple random sample of employees. Data was analyzed by using suitable descriptive and analytical statistical methods available at SPSS. Results of data analysis revealed that there is strong and positive relationship between strategic planning and crisis management. It was found that managing crisis is greatly influenced by strategic planning. Based on that, it was recommended to support strategic planning in public organizations.
Keywords: Strategic planning; Crisis Management Strategies; Public organizations